2015
DOI: 10.5137/1019-5149.jtn.12812-14.0
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variability in termination of basilar artery in human cadaveric brain

Abstract: AIm:The basilar artery (BA) is the prominent median vessel of the vertebrobasilar circulation and usually terminates into two posterior cerebral arteries forming the posterior angle of the Circle of Willis (CW). To tackle different variations of CW, basilar artery acts as a guideline for neuroradiologists and neurosurgeons. Basilar termination is the most frequent site of aneurysm. Abnormalities at the site of termination may compress the oculomotor nerve. Variations at the termination may complicate surgeries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
3
12
0
Order By: Relevance
“…High Willis asymmetry rates in bleeding aneurysms confirm the relationship between hemodynamic disturbance due to asymmetric configuration and aneurysm formation and rupture (3,4,7,12,13,15,23,26,29,33). In bleeding ACoA aneurysms, Stojanovic et al (33) reported that the asymmetry presence accounted for 72.7%; morphological changes were present in the A1 segment (44%) and mainly on the right side (60%).…”
Section: Bleeding and Non-bleeding Aneurysmsmentioning
confidence: 85%
See 2 more Smart Citations
“…High Willis asymmetry rates in bleeding aneurysms confirm the relationship between hemodynamic disturbance due to asymmetric configuration and aneurysm formation and rupture (3,4,7,12,13,15,23,26,29,33). In bleeding ACoA aneurysms, Stojanovic et al (33) reported that the asymmetry presence accounted for 72.7%; morphological changes were present in the A1 segment (44%) and mainly on the right side (60%).…”
Section: Bleeding and Non-bleeding Aneurysmsmentioning
confidence: 85%
“…Krayenbuhl and Yaşargil (15) reported vertebral artery fenestration or anomalous termination. Gunnal et al (7) found morphological variations in termination in 17.64% of the cases. The prevalence of fenestrations of the intracranial VB system was reported to be between 1.17% and 2.77% (7,13,37).…”
Section: Bleeding and Non-bleeding Aneurysmsmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar studies have reported the same variations though with a varying prevalence rates. 10,11 Ogeng'o et al 11 reported 82.1% normal bifurcation in a black Kenyan population and Gunnal et al 10 82.5% in a turkish population. These two studies reported a significantly higher prevalence of bifurcations as compared with our study.…”
Section: Discussionmentioning
confidence: 98%
“…Several morphological studies have documented the terminal end variations of the basilar artery among various populations including bifurcations, trifurcations, quadrifurcations and pentafurcations. [9][10][11][12] These multiple branching patterns are believed to be lodging points for thromboembolic phenomena and pathologies like atherosclerosis and aneurysms. Aneurysms with multiple branching patterns at such points would lead to nerve compressions resulting into optical abnormalities.…”
Section: Introductionmentioning
confidence: 99%